2014
DOI: 10.4103/0974-8237.135213
|View full text |Cite
|
Sign up to set email alerts
|

Orthosis for thoracolumbar burst fractures without neurologic deficit: A systematic review of prospective randomized controlled trials

Abstract: Background:Traditionally, conservative treatment of thoracolumbar (TL) burst fractures without neurologic deficit has encompassed the application of an extension brace. However, their effectiveness on maintaining the alignment, preventing posttraumatic deformities, and improving back pain, disability and quality of life is doubtful.Objective:The objective was to identify and summarize the evidence from randomized controlled trials (RCTs) to determine whether bracing patients who suffer TL fractures adds benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“… 9 Fewer reviews have been published about conservative treatment options, for example, on the usefulness of orthoses. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“… 9 Fewer reviews have been published about conservative treatment options, for example, on the usefulness of orthoses. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…Multiple prior studies have demonstrated the lack of benefit associated with bracing for stable TL fractures, and this study did not aim to replicate those findings. 7,9,11,14 In this study, providers were not compelled to follow the pathway, and fracture stability determination and treatment was ultimately up to their clinical judgment. A greater degree of change may have been observed had we been more stringent in our efforts to ensure compliance with the pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Patients are encouraged to apply the spinal brace at all times unless they are lying down, for example, during bedrest. Typically, these braces are usually fixed and rigid (for example, TLSO, thoracolumbar spinal orthosis, see Figure 3 ) [ 21 ].…”
Section: Passive Spine Braces In the Treatment Of Osteoporotic Spimentioning
confidence: 99%